Implemetasi algoritma fletcher-reeves dalam menganalisa nilai ekspor menurut golongan sitc - Riski Wulandari; Mochamad Wahyudi; Lise Pujiastuti; Solikhun (Trigin Publisher, 2022)
Indonesia has a lot of natural resources, so Indonesia uses them by conducting trade activities between countries. Export is a movement to sell or send goods from within the country to abroad. Conjugateigradient Fletcher-Reeves Algorithm According to some references, it is an appropriate development technique compared to the backpropagation strategy because this strategy can speed up the preparation time to arrive at the minimum convergence value. Furthermore, this research shows whether the algorithm performs well and can provide productive assembly results when used to solve problems because the value corresponds to the Standard International Trade Classification (SITC) class. The prediction models used are 5-10-1, 5-15-1, 5-20-1, 5-25-1 and 5-30-1. MSE of 0.00287273, the minimum among the other four models. The model can be used because it produces a fast combination and a fairly short period